Hereditary ovarian cancer: BRCA-Associated risk, screening limitations, and risk-reduction strategies - Flavia Drozdz; Mateus Souza Cardoso; Natacha Carmona Cordeiro Alves; Luana Lorenski; Fernanda Tobar Lo Ré Chambray; Livia Azevedo Leonardi (International Health Sciences Review, 2026)
Hereditary susceptibility accounts for a clinically meaningful proportion of epithelial ovarian, fallopian tube, and primary peritoneal cancers, with pathogenic variants in BRCA1 and BRCA2 producing the largest and best-characterized risks. This narrative and critical review examines how BRCA-associated risk should influence genetic identification, ovarian cancer surveillance, and preventive decision-making. Literature searches conducted in August 2026 prioritized clinical guidelines, systematic reviews, prospective cohorts, pivotal screening studies, and contemporary trials of risk-reducing surgery. Evidence consistently shows that BRCA1 and BRCA2 carriers have markedly different age-specific tubo-ovarian cancer risks, which supports gene-specific timing of risk-reducing salpingo-oophorectomy after completion of childbearing. Screening based on cancer antigen 125 and transvaginal ultrasonography may detect some cancers earlier, particularly when longitudinal algorithms are used, but it has not been shown to reduce mortality and should not be considered an equivalent alternative to preventive surgery. Salpingo-oo phorectomy substantially reduces tubo-ovarian cancer risk and is associated with improved survival, although premature menopause, quality-of-life effects, and residual primary peritoneal cancer risk require anticipatory management. Salpingectomy with delayed oophorectomy improves menopause-related outcomes in prospective studies, but its oncologic non-inferiority remains unproven. Effective prevention therefore depends on timely genetic testing, individualized counseling, technically complete surgery, and careful management of reproductive and menopausal consequences.